Production of Starch-Based Flexible Food Packaging in Developing Countries: Analysis of the Processes, Challenges, and Requirements - Johanna Garavito; Clara P. Peña-Venegas; Diego A. Castellanos (Foods)
Biodegradable packaging offers an affordable and sustainable solution to global pollution, particularly in developing countries with limited recycling infrastructure. Starch is well suited to develop biodegradable packages for foods due to its wide availability and simple, low-tech production process. Although the development of starch-based packaging is well documented, most studies focus on the laboratory stages of formulation and plasticization, leaving gaps in understanding key phases such as raw material conditioning, industrial-scale molding, post-production processes, and storage. This work evaluates the value chain of starch-based packaging in developing countries. It addresses the challenges, equipment, and process conditions at each stage, highlighting the critical role of moisture resistance in the final product’s functionality. A particular focus is placed on replacing single-use plastic packaging, which dominates food industries in regions with agricultural economies and rich biodiversity. A comprehensive analysis of starch-based packaging production, with a detailed understanding of each stage and the overall process, should contribute to the development of more sustainable and scalable solutions, particularly for the replacement of single-use packages, helping to protect vulnerable biodiverse regions from the growing impact of plastic waste.